Anti-Nogo-A Immunotherapy Does Not Alter Hippocampal Neurogenesis after Stroke in Adult Rats - Shepherd, Daniel J.; Tsai, Shih-Yen; O'Brien, Timothy E.; Farrer, Robert G.; Kartje, Gwendolyn L. (Frontiers in Neuroscience, 2016)
Ischemic stroke is a leading cause of adult disability, including cognitive impairment. Our laboratory has previously shown that treatment with function-blocking antibodies against the neurite growth inhibitory protein Nogo-A promotes functional recovery after stroke in adult and aged rats, including enhancing spatial memory performance, for which the hippocampus is critically important. Since spatial memory has been linked to hippocampal neurogenesis, we investigated whether anti-Nogo-A treatment increases hippocampal neurogenesis after stroke. Adult rats were subject to permanent middle cerebral artery occlusion followed one week later by two weeks of antibody treatment. Cellular proliferation in the dentate gyrus was quantified at the end of treatment, and the number of newborn neurons was determined at 8 weeks post-stroke. Treatment with both anti-Nogo-A and control antibodies stimulated the accumulation of new microglia/macrophages in the dentate granule cell layer, but neither treatment increased cellular proliferation or the number of newborn neurons above stroke-only levels. These results suggest that anti-Nogo-A immunotherapy does not increase post-stroke hippocampal neurogenesis.